2015
DOI: 10.1088/0957-4484/27/4/045102
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and characterization of ferritin for nanomaterial applications

Abstract: Ferritin is a ubiquitous iron storage protein utilized as a nanomaterial for labeling biomolecules and nanoparticle construction. Commercially available preparations of horse spleen ferritin, widely used as a starting material, contain a distribution of ferritins with different iron loads. We describe a detailed approach to enrich for differentially-loaded ferritin molecules by common biophysical techniques such as size exclusion chromatography and preparative ultracentrifugation, and characterize these prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The relaxivity of ferritin nanoparticles is strongly dependent on the amount of Fe contained in the apoferritin shell [21,94,95]. The iron nanoparticles, stored in the ferritin cages, are either in an antiferromagnetic or super paramagnetic form [96,97], which results in an unique effect on the relaxation of water as detected by MRI [98].…”
Section: Ferritin Nanoparticles Used In Molecular Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The relaxivity of ferritin nanoparticles is strongly dependent on the amount of Fe contained in the apoferritin shell [21,94,95]. The iron nanoparticles, stored in the ferritin cages, are either in an antiferromagnetic or super paramagnetic form [96,97], which results in an unique effect on the relaxation of water as detected by MRI [98].…”
Section: Ferritin Nanoparticles Used In Molecular Imagingmentioning
confidence: 99%
“…The ferritin nanoparticles used in constrained synthesis, nanodevices [5,1721], have been summarized in several excellent review articles and will not be discussed here. In this article, we will focus on the use of ferritin nanoparticles in the fields of drug delivery, vaccine development, bioassay, disease diagnosis and therapy with molecular imaging methods (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous ice nucleation is considered to arise from the ability of surfaces to order water molecules in an icelike pattern. The arrangement of water molecules at a surface depends on surface charge and functional groups (Glatz and Sarupria, 2016;Abdelmonem et al, 2017;. A relevant role is attributed to surface OH and NH groups that are able to form hydrogen bonds to water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…
Ferritin is assembled from sub-chains into a spherical shape. We have found that the number of sub-chains is generally 3,6,8, 12, 24, 36, and the corresponding spherical volume (outer diameter) is also different. In this paper, using the protein structural data from PDB website, linear regression was carried out to model the relationship between sub-chain number and outer diameter of 25 ferritins by calculation and analysis, but the results were not ideal.
…”
mentioning
confidence: 87%
“…Ferritin proteinscan self-assemble into multi-subunit, nano-scale cages. They are also highly amenable through genetic and chemical modifications, which have attracted much recent attention in drug delivery studies and nanomaterial science [6]. In our previous research, site-directed mutagenesis on N-and C-termini of ferritin 3kx9 led to an increase in the volume of self-assembled protein cages [7].…”
mentioning
confidence: 99%